Effect of some organic acid on the quality of eğrez (vimbia vimbia tenella) fish - Abdullah Diller; Behire Işıl Işıklı; Ahmet Güner; Yusuf Doğruer (Eurasian Journal of Veterinary Sciences)
In this investigation, it was earned out to determine the effect of benzoic, sorbic and lactic acide added to pickling solu!ion before smoking on the quality of Eğrez fish (Vimbia vimbia tenella). For this purpose, the fish were kept in four different pickling solutions for 10 h ai 4°C. The first contained only 20% NaCI solution (control) and the others contained 20% NaCI with 0.5% benzoic acide, 0,1% sorbic acide and 0.03% lactic acide. The fish were smoked at 30°C for 30 min, 1 h al 50"C and 1 h at SO'C. Afterwards, the fish were vacuum packaged and stored at 4°C for 45 days. The samples were analyzed lor chemical, microbiological, and organoleptica) properties on days 1W, 14th, 22^. 30th and 45th dunng storage. The fish were analyzed for chemical and microbiological propetrties before salting. It was determined that organic acid added to pickling solution before salting caused to decrease in pH values {P<0.001) and in numbers of Staphylococcus-Micrococcus (P<0.001). However, a significant increase was observed in TBA values (P<0,001) of the samples. Lactic actde application was more effective on total psycrophilic aerobic microorganisms (P<0.001), colilorm bacteria (P<0.001), flavor (PcO.OI). texture (PcO.OOl, P<0.05), and overall acceptability (P<0.05) than the others. Sorbic acide application caused to decrease in TVB-N levels, Sorbic and lactic acide groups received the highest color No significant effoct of benzoic acide application was found on the quality during Ihe storage period. In conclusion, il was determined that use of lactic acide in pickling before smoking has positive effects on the quality and shelf-life of fish than the sorbic and benzoic acide.